Supporting nurse health champions: developing a 'new generation' of health improvement facilitators - Blake, Holly; Chambers, D. (Sage, 2011)
In efforts to respond to key government public health initiatives for settings-based health promotion, the ‘Workplace Health Champion’ role has emerged as a method of promoting health within the UK healthcare setting. Health promotion techniques used by these individuals are based on psychological theories that are known to motivate people to change behaviours associated with ill-health. Health Champions, like NHS Health Trainers, assist individuals in setting personal goals to change behaviours thus encouraging empowerment and individual sense of control over personal health and wellbeing. This article describes the developing role of NHS Health Champions in the public health agenda. Nurses are well placed to promote healthy lifestyles to their patients and clients although evidence suggests that healthcare staff do not always heed their own advice, despite being viewed as role models for health amongst the general public. Nurses are proposed here as both targets and facilitators of health promotion and are advocated as ideal workplace health champions within the NHS. This might be achieved through structured educational training in health improvement for nurses and other healthcare professionals. We propose that health service managers consider supporting healthcare professionals to become workplace health champions.